Analysis of the impact of sustainable and blue entrepreneurship in the transversal competences of Higher Education (SciComm Report, 2023)
Social entrepreneurship is currently producing a progressive interest in society, because it contributes to generating value by responding and seeking innovative solutions to social needs related to economic, social or environmental aspects. When these initiatives have the additional objective of respecting the marine environment, favoring its conservation and the sustainable development of the regions in which it is framed, we would be talking about blue social entrepreneurship. The university has become one of the fundamental pillars in the development and promotion of entrepreneurship and social and blue entrepreneurship, fundamentally it is through the transversal skills that appear in the Degree reports that the training of graduates in entrepreneurship and sustainable development. Our study focuses on the analysis of the transversal competences of the different Andalusian universities by branches of knowledge in the field of entrepreneurship and sustainable development. The reports and schedules of the Degree subjects contain many concepts, both theoretical and practical, that must also be covered, and that make teaching on transversal skills difficult. To carry out a comparative analysis of the transversal competences, a post hoc test has been carried out, which was applied to a total of 78 teaching schedules (n1=78) from 41 different university degrees. The results indicate that blue entrepreneurship is partially included in the cross-cutting skills of university degrees, with the branches of knowledge “Social and Legal Sciences” and “Science” where they appear the most. Based on the results, it is considered necessary that in the university environment a higher level of individual and global development be favored and be an engine of change and social transformation.
Keywords: Transversal skills; blue entrepreneurship; teaching methods; sustainability; higher education